Entre Clio e Kirós: organização e vivência do tempo de trabalho de professores gestores da Universidade Federal do Ceará – Campus Sobral - Sabóia, Iratan Bezerra de (2019)
This thesis has as main objective to investigate the impacts of the organization of working time of UFC professors who hold management positions. With this purpose, we delimit our universe of research to the professors-managers who occupy positions of directors, coordination and their vices for at least six months in the function in the Campus of Sobral. The research was developed in four stages: integrative review of literature in the portals SciELO and CAPES; field survey interviews; budget time survey, and semi-structured interviews with content analysis. In the first stage only twenty texts that met the inclusion / exclusion criteria returned, it was exposed that there is a small national production on the subject, as well as an inferior and concentrated production in the southeast of the country on temporality and higher level teaching work. In the second stage we constructed the categories of analysis: invisible activity; naturalized activity; precariousness and flexibility; intensification of working time; colonization of working time and social solvency by working time. In the third stage, a quantitative budget time instrument was applied, in which a high workload of professors-managers was evidenced; the naturalization of some activities; prioritization of teaching, management, guidance and research activities and the recurrence of the same professors in the management positions. The last stage of field research revealed a process of precariousness and flexibility of work; intensification of work; the invisibility of some activities of the teachers searched; the naturalization of activities less significant to them; the colonization of working time over other social times, and a breakdown of social relations as a result of working time and the prioritization of activities: teaching because of the desire of these teachers, management by imposition of position and research in the reason for their careers.It is concluded that the teacher-managers are submitted to high workloads; divided into activities that require different knowledge and evaluation criteria; with intensified works that result from occupying other social times that could be destined to other activities; that this framework erodes social relations including those of their families, causing the possible restriction of their social circles and health problems.